2006
DOI: 10.1158/1078-0432.ccr-04-1752
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Activation of Stat3 Signaling Induces Survivin Gene Expression and Confers Resistance to Apoptosis in Human Breast Cancer Cells

Abstract: Purpose: Signal transducer and activator of transcription 3 (Stat3) protein is persistently activated in breast cancer and promotes tumor cell survival. To gain a better understanding of the role of constitutive Stat3 signaling in breast cancer progression, we evaluated the expression profile of potential Stat3-regulated genes that may confer resistance to apoptosis. Experimental Design: Stat3 signaling was blocked with antisense oligonucleotides in human MDA-MB-435s breast cancer cells and Affy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
381
1
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 496 publications
(405 citation statements)
references
References 47 publications
18
381
1
5
Order By: Relevance
“…The response of cells to apoptotic stimuli depends on the balance between pro-and anti-apoptotic members of apoptosis family. The overexpression of both Bcl-X L and Bcl-2, survivin have been shown to prevent mitochondrial apoptosis in tumor cells [6,12]. Western blot analysis demonstrated that CDDOMe treatment results in the down regulation of these antiapoptotic proteins in paclitaxelresistant cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The response of cells to apoptotic stimuli depends on the balance between pro-and anti-apoptotic members of apoptosis family. The overexpression of both Bcl-X L and Bcl-2, survivin have been shown to prevent mitochondrial apoptosis in tumor cells [6,12]. Western blot analysis demonstrated that CDDOMe treatment results in the down regulation of these antiapoptotic proteins in paclitaxelresistant cells.…”
Section: Discussionmentioning
confidence: 99%
“…There is no therapy to overcome drug resistance in ovarian cancer. The development of chemoresistance is associated with many events, such as defective apoptotic signaling in response to drugs, overexpression of antiapoptotic proteins such interleukin 6 (IL-6), Bcl-2, BcL-X L , or survivin, and overexpression of multidrug resistance (MDR) gene protein pgp1 [6][7][8][9]12]. Successful management of ovarian cancer would be greatly aided by novel agents that interfere with both intrinsic and acquired mechanisms of drug resistance mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…24 The relationship between survivin and STAT3 is somewhat more complicated than that between survivin and p53. STAT3 directly binds to and regulates the survivin promoter, 63 and STAT3 activation induces survivin expression and rescues cells from apoptosis. 25,63 However, survivin can also bind to STAT3 dimers and repress STAT3 transactivation of target gene promoters.…”
Section: Discussionmentioning
confidence: 99%
“…STAT3 directly binds to and regulates the survivin promoter, 63 and STAT3 activation induces survivin expression and rescues cells from apoptosis. 25,63 However, survivin can also bind to STAT3 dimers and repress STAT3 transactivation of target gene promoters. 64 Thus, clarifying the mechanism underlying the association of STAT3-survivin coexpression with better overall survival and progression-free survival is difficult.…”
Section: Discussionmentioning
confidence: 99%
“…3C). Since expression of cyclin D1, Bcl-xL and Survivin required positive transcriptional control of STAT3 [30,31], the observed changes in these levels were expected. In contrast, levels of anti-apoptotic protein XIAP did not notably decrease after RSV treatment in LU1205.…”
Section: Signaling Pathways Affected By Rsv In Lu1205 Melanoma Cellsmentioning
confidence: 92%